Substantial differences in genetic diversity and spatial structuring among (cryptic) amphipod species in a mountainous river basin. (18th June 2020) - Weigand, Alexander M.; Michler‐Kozma, Diana; Kuemmerlen, Mathias; Jourdan, Jonas
Abstract: Recent advances in molecular methods foster the documentation of small spatial scale biological diversity over large geographical areas. These advances allow to correctly record α‐diversity, but also enable biomonitoring that describes intraspecific molecular diversity, providing valuable insights into the contemporary history of species. Such information is essential for the accurate monitoring of freshwater communities and provides a promising tool to identify conservation priorities at various spatial scales. Here, we combined morphological species determinations with genetic characterisation via DNA barcoding and species distribution modelling. We aimed to investigate whether closely related amphipod species occupying overlapping ecological niches and occurring in partial sympatry, demonstrate similar spatial patterns of intraspecific genetic diversity and share comparable population histories. Therefore, we characterised the amphipod fauna within the Kinzig catchment (1, 058 km 2, Hesse, Central Germany) that is a tributary of the Main River and part of the long‐term ecological research network using genetics. Our genetic analysis revealed two more taxonomic entities than previously known. The most common species was Gammarus fossarum clade 11 (or type B), followed by Gammarus roeselii clade C, Gammarus pulex clade D, G. pulex clade B and a very rare previously unknown lineage within the G. fossarum ‐species complex, which we refer to as G. fossarum clade RMO. These five taxa differed in their intraspecific genetic diversity, with G. fossarum clade 11 demonstrating the highest diversity and having a prominent small‐scale pattern with endemic haplotypes in headwater regions. Distributions were predicted for the three most abundant molecularly identified species. The upstream reaches maintained high intraspecific α‐ and β‐diversity, pointing towards a more complex population structure of G. fossarum clade 11. This highlights the importance of considering intraspecific diversity for the conservation of individual species. DNA‐based species distribution models shed light on species‐specific habitat preferences, and showed spatial distribution patterns that supported ecological inference and conservation management. Barcoding specimens prior to modelling can increase robustness and performance of distribution models as juveniles can be incorporated, and cryptic species complexes disentangled. Our integrative study contributes to the further development of science‐informed and holistically considered effective conservation measures. Some poorly dispersing hololimnic species may serve as representatives for our understanding of the natural history of the local communities in headwater regions—and their protection. Intraspecific genetic diversity should be considered in conservation management decisions as it can provide valuable information on past and present population demography, connectivity, and recovery processes of species—information that rarely can be achieved by traditional monitoring approaches.